The need for development of dynamic capabilities’ perspectives as a panacea to poor performance of SMEs in less developed economy (Nigeria). - Samson, Abiodun Tope (IJRDO - Journal of Business Management, 2018)
A firm’s constant pursuit of the renewal, reconfiguration and recreation of resources, capabilities and core capabilities to address environmental change of capabilities that are conducive to longterm performance rather than simply a subset of the capabilities would enhance and sustain competitive advantage. The major pre-occupation of this paper was to consider the antecedents, roles and importance of SMEs in less developed economies (i.e. Nigeria) and employ dynamic capabilities’ perspective as therapy to be used and overcome SMEs’ poor performance .